2021
DOI: 10.1039/d1sc01276b
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational exciton delocalization precludes the use of infrared intensities as proxies for surfactant accumulation on aqueous surfaces

Abstract: Surface-sensitive vibrational spectroscopy is a common tool for measuring molecular organization and intermolecular interactions at interfaces. Peak intensity ratios are typically used to extract molecular information from one-dimensional spectra but...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that IRRAS band intensities are not expected to increase linearly with surface concentration due to exciton delocalization and the loss of many small bands in the IRRAS baseline. 34 As a result, and due to the potential impact of different cations on the interfacial structure of water, we have not attempted to use IRRAS in a quantitative way to compare the efficacy of different salts in driving AAs to the surface. Nevertheless, our data corroborate our π measurements by showing that AA peaks are enhanced in the presence of salts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that IRRAS band intensities are not expected to increase linearly with surface concentration due to exciton delocalization and the loss of many small bands in the IRRAS baseline. 34 As a result, and due to the potential impact of different cations on the interfacial structure of water, we have not attempted to use IRRAS in a quantitative way to compare the efficacy of different salts in driving AAs to the surface. Nevertheless, our data corroborate our π measurements by showing that AA peaks are enhanced in the presence of salts.…”
mentioning
confidence: 99%
“…A representative result is given in Figure where several (negative) peaks show greater intensity in the presence of 3 versus 0 m CaCl 2 . It has been demonstrated that IRRAS band intensities are not expected to increase linearly with surface concentration due to exciton delocalization and the loss of many small bands in the IRRAS baseline . As a result, and due to the potential impact of different cations on the interfacial structure of water, we have not attempted to use IRRAS in a quantitative way to compare the efficacy of different salts in driving AAs to the surface.…”
mentioning
confidence: 99%
“…Only effects that occur at the surface can be observed, and trends can be analysed to improve samplepreparation methods. The explanation as to why they occur cannot be understood using standard cryo-EM experiments alone and requires complementary approaches such as infrared spectroscopy or dynamic surface-tension measurement studies (Carter-Fenk et al, 2021;Tang et al, 2020). Alternative approaches to sample preparation have been proposed in recent years to overcome the preferred orientation issue (Esfahani et al, 2024;Drulyte et al, 2018;Glaeser & Han, 2017;Jain et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Only the effects that occur at the surface can be observed, and trends can be analysed to improve the sample preparation methods. The explanation as to why they occur cannot be understood using standard cryo-EM experiments alone and requires complementary approaches such as infrared spectroscopy or dynamic surface tension measurement studies (Carter-Fenk et al, 2021; F. Tang et al, 2020). Alternative approaches to sample preparation have been proposed in recent years to overcome the preferred orientation issue (Esfahani et al, 2024 ;Drulyte et al, 2018; Glaeser & Han, 2017; Jain et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Only the effects that occur at the surface can be observed, and trends can be analysed to improve the sample preparation methods. The explanation as to why they occur cannot be understood using standard cryo-EM experiments alone and requires complementary approaches such as infrared spectroscopy or dynamic surface tension measurement studies (Carter-Fenk et al, 2021;F. Tang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%